Prandtl and capillary effects on heat transfer performance within laminar liquid-gas slug flows - Howard, J; Walsh, P; Walsh, E (2011)
This paper investigates a two-phase non-boiling slug flow regime for the purposes of enhancing heat transfer in microchannel heat sinks or compact heat exchangers. The primary focus is upon understanding the mechanisms leading to enhanced heat transfer and the effect of using different Prandtl number fluids, leading to variations in Capillary number. Experimental work was conducted using Infrared thermography and results are presented in the form of Graetz solution, spanning both the thermal entrance and fully developed flow regions. Nusselt numbers enhancements were observed throughout when data was reduced to account for void fraction. However, the gaseous void was also noted to demonstrate an artificial increase with greater thicknesses of the liquid film, due to higher Capillary numbers. Up to 600% enhancement in heat transfer rates were observed over conventional Poiseuille flow. This was verified through Nusselt number measurements over inverse Graetz number ranges from 10-4 to 1 and slug length to channel diameter ratios from 0.88 to 32. Varying Prandtl and Capillary numbers caused notable effects in the transition region between entrance and fully developed flows. Significant Nu oscillations were observed for low Pr fluids due to internal circulation within the slug. However, these oscillations are observed to be damped out when higher Prandtl number fluids are employed. The thickness of the liquid film surrounding the gas bubbles is shown to have a significant influence on heat transfer performance. Overall, this study provides a greater understanding of the mechanisms leading to significant enhancements in heat exchange devices employing two-phase gas-liquid flows without boiling. © 2011 Elsevier Ltd. All rights reserved.